Pendampingan Guru Taman Pendidikan al-Qur’an dalam Peningkatan Pemahaman Bacaan Melalui Program Tahsin dan Tadabbur di Desa Mojopuro Gresik - Muhammad Shohib; Imam Nur Aziz (Academia Publication, 2024)
The purpose of this study is to improve the ability to read the Quran by TPQ teachers through Tahsin training, where it is hoped that TPQ teachers in Mojopuro Village can read the Quran with correct tajweed through intensive training classes guided by competent ustaz to ensure that the correct standards of reading the Quran can be applied. The service method in this program uses a Learning Service approach, namely with the Implementation Stages and Needs Identification, Program Planning, Training Implementation, Assistance and Evaluation, Learning Community Development, and Reflection and Report Preparation. The results of the service show that the TPQ teacher assistance program in improving the understanding of the Quran through the Tahsin and Tadabbur programs in Mojopuro Gresik Village has succeeded in achieving the expected goals. Periodic evaluations showed that the program was running as planned and achieved significant results with an evaluation score of 8.5 on a scale of 1-10, as well as an increase in teachers' confidence and competence from a scale of 5 before the program to 9 after the program. For program development, it is recommended to increase intensive practice and mentoring sessions, as well as continuous support from the community and service team.